Characterisation of the heat shock protein Tid and its involvement in stress response regulation in Apis cerana - Li, Guilin; Zhang, Chenghao; Wang, Hongfang; Xia, Wenli; Zhang, Xinyi; Liu, Zhenguo; Wang, Ying; Zhao, Hang; Xu, Baohua (Frontiers in Physiology, 2022)
The impact of various environmental stresses on native Apis cerana cerana fitness has attracted intense attention in China. However, the defence responses of A. cerana cerana to different stressors are poorly understood. Here, we elucidated the regulatory mechanism mediated by the tumorous imaginal discs (Tid) protein of A. cerana cerana (AccTid) in response to stressors. AccTid is a homologous gene of human Tid1 and Drosophila Tid56, contains a conserved J domain and belongs to the heat shock protein DnaJA subfamily. The degree of AccTid induced expression was increased under temperature increases from 40°C to 43°C and 46°C, indicating that the upregulation of AccTid plays an important role when A. cerana cerana is exposed to heat stress. Interestingly, contrary to the results of heat stress treatment, the transcriptional level of AccTid was inhibited by cold stress and some agrochemical stresses and showed no significant change under ultraviolet ray stress. These results suggested that the requirement of A. cerana cerana for Tid differs markedly under different stress conditions. In addition, knockdown of AccTid increased the mRNA levels of many antioxidant genes. The upregulation of these antioxidant genes may be a functional complement of AccTid knockdown. In summary, AccTid plays a crucial role in A. cerana cerana stress responses and may mediate oxidative damage caused by various stresses. Our findings will offer fundamental knowledge for further investigations of the defence mechanism of A. cerana cerana against environmental stresses.